The Influential Factors of TQM and TPM Implementation on Manufacturing Industry Performance (MIP) - Al Maazmi, Abdalla; Al Hamadi, Abdallah (Journal of Advanced Industrial Technology and Application, 2021)
The demand for quality is the one crucial factor for businesses in today’s highly competitive market, to thrive in this ever expanding global market. As a result of intense global competition, Total quality management (TQM) has been created. Most of the previous papers show that TQM is very related to business success. However, the analysis of the Total productive maintenance (TPM) as mediator between TQM and MIP not widely found and previous researches were commonly regarded as general instruments and techniques without particular emphasis on improvement styles. This paper aims to suggest the relationship between TQM and MIP through mediating impact of TPM. The methodology adopted for this research was to use a review of existing literature, this paper explores the theories of TQM and TPM to provide useful information to ensure effective management of manufacturing industry. The key contribution of this paper is to develop a conceptual model to describe the cause- effect relationship between TQM, TPM activities and MIP. The implication of the proposed conceptual model would help academics and policy makers in the industry to better understand the relationship between activities.